Effect of 1174® Silage Inoculant on the fermentation of corn silages - Bolsen, K.K.; Lin, C.; Brent, B.E.; Bradford, J.E.; Feyerherm, A.M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effect of 1174® Silage Inoculant on the ensiling process was studied using three Pioneer corn hybrids. All hybrids fermented rapidly, and 1174 did not significantly influence any of the fermentation characteristics during the 120 days. The epiphytic lactic acid bacteria (LAB) counts on the chopped corn plants were high; 14 times greater than the numbers of LAB provided by the inoculant. Although during fermentation, statistically significant differences occurred among the hybrids for fermentation end-products, no observed trends suggested that hybrid effects were real.
Keywords: Beef; Silage; Corn; Bacterial; Inoculant